Self-care plant system / Muhammad Umar Aiman Mohd Sabri - Mohd Sabri, Muhammad Umar (2024)
Houseplants are a type of plant that grows indoors. Not only do these plants enhance the overall appearance of a space, but also boost moods, increase creativity, and eliminate air pollutants. People also grow houseplants to reduce the stress they get from working or other daily activities. Even though houseplants have many benefits, they are still plants that need to be watered and taken care of. This is going to be a problem for people who work a lot or have a busy schedule. Thus, to overcome this problem, an automatic watering system is created so that the plants don’t need constant human attention. This research proposed a self - watering plant system with environmental monitoring. The objective of this research is divided into 2 parts. The first part is the hardware development that consists of three sensors which are Soil Moisture Sensor, temperature, and humidity sensor (DHT11) and an ultrasonic sensor for measuring water tank levels. These sensors are used to monitor the condition of the plant’s soil by combining with a microcontroller like the ESP32. The second part is to provide the plant with water by using a small watering pump and to display the measured value of the DHT11 using LCD. This system also uses IoT technology to transfer data from the DHT11 and the Ultrasonic sensors to the owner’s mobile phone using features ESP32. Therefore, this system will help those who love plants and flowers but doesn’t have the time to take care of it.